Artificial oxygen carriers based on perfluorodecalin-filled poly(n-butyl-cyanoacrylate) nanocapsules. (May 2014) - Stephan, Claudia; Schlawne, Carolin; Grass, Stefan; Waack, Indra N.; Ferenz, Katja B.; Bachmann, Michael; Barnert, Sabine; Schubert, Rolf; Bastmeyer, Martin; de Groot, Herbert; Mayer, Christian
Abstract Poly(n-butyl-cyanoacrylate)-nanocapsules filled by perfluorodecalin (PFD) are proposed as potential oxygen carriers for blood substitute. The capsule dispersion is prepared via interfacial polymerisation from a PFD emulsion in water which in turn is generated by spontaneous phase separation. The resulting dispersion is capable of carrying approximately 10% of its own volume of gaseous oxygen, which is approximately half of the capacity of human blood. The volumes of the organic solvents and water are varied within a wide range, connected to a change of the capsule radius between 200 and 400 nm. The principal suitability of the capsule dispersion for intravenous application is proven in first physiological experiments. A total amount of 10 ml/kg body weight has been infused into rats, with the dispersion supernatant and a normal saline solution as controls. After the infusion of nanocapsules, the blood pressure as well as the heart rate remains constant on a normal level.